Calculs en élastoplasticité par une technique de minimisation - Cornuault, Christian (European Journal of Computational Mechanics, 2001)
An original numerical method is presented, which was implemented for the structural analysis of components stressed in possibly both large displacements and plasticity domains, as it is the case for metallic panel plastic buckling or post-buckling. Thanks to a suitable formulation and implicit numerical schemes, one can exhibit a mechanical potential function, from which elastic plastic equilibrium equations and normality evolution laws are derived. Taking advantage of this potential function, an efficient numerical method, which involves minimisation by means of an exact line-search, was developed, thus enabling direct obtention of small and large displacement solutions, and, hence, direct obtention of plastic post buckled states as well as elastic ones. Validation and computation efficiency, industrially speaking, have already been proved through a several year current practice.